INOVASI ICE CRUSHER MACHINE SEBAGAI UPAYA EFISIENSI PROSES PENGAWETAN BEBEK DI RUMAH POTONG UNGGAS DESA SUKONATAR - Rizal Yulianto; Dimas Agung Budianto; Adam Riky Pratama; Mauli Diana; Indana Zulfa; Ika Yuniwati (LPPM Universitas Bina Bangsa, 2023)
Manual crushing of ice cubes has the result of breaking each ice cube is not the same. This can affect the preservation process. The methods used in this service are first survey and observation, machine development, evaluation, socialization, and mentoring. The survey activity was carried out in Sukonatar Village, Srono District, Banyuwangi Regency, with the target object being the Mr. Edi Sugara Poultry Slaughterhouse. The result of the survey of problems experienced by poultry slaughterhouses is the lack of knowledge and understanding of partners about ice cube crushing technology. Then the second activity continued on engine development (Ice Crusher Machine) and engine evaluation. This activity produces machines with a capacity of 300 kg / hour. The next activity is socialization and mentoring of partners. In the duck preservation process, a span of 1 month, partners can make cost efficiencies of Rp 300,000 and 10 hours in the ice crushing process